Política Nacional de Saúde Integral da População Negra (PNSIPN): o (des)conhecimento dos(as) profissionais universitários(as) da saúde mental - Rosa, Jéssifran Silveira (2023)
This paper has as theme the (lack of) knowledge regarding the health of black population by universities professionals of mental health. It researched what knowledge the different university professionals who integrated multidisciplinary teams in two Psychosocial Attention Centers (CAPS) had related to the National Policy of Black Population Integrative Health (PNSIPN), its relation to their qualification processes (both in the undergraduate and permanent qualification) and professional performance. The considered hypothesis was that most professionals did not have or had little knowledge regarding PNSIPN since undergraduate and permanent qualification courses have incorporated neither the content related to the previously mentioned National Policy nor what is determined by the National Educational Curriculum Guideline to the Education Related to Ethinic-Racial Relationships (DCNERER) as well as Afro-Brazilian and African History and Culture. The theoretical reference is mainly founded in intellectuals who discuss health, mental health, racism and colonialism, such as Frantz Fanon, Lélia Gonzalez, Deivison Mendes Faustino, Rachel Gouveia Passos and others. This work includes bibliographic and documental research, questionnaire application and interviews (authorized by the Research Ethics Committee) with eight (8) university professionals from different areas of knowledge who work in two different CAPS managed by the Dr. Cândido Ferreira Health Service in Campinas/SP. It begins with the Brazilian Psychiatric Reform, the disregard with specificities of the black population which determine the proposal of a policy to that group, that black people have a higher percentage of representation in institutions of mental health service, from asylum to the current CAPS. Although the discussion of social determinants means a greater vulnerability of the black population, including psychosocial effects of racism, it is found that the implementation of PNSIPN is still a challenge and there is absence of its discussion in undergraduate, postgraduate courses and/ or permanent education. Data revealed that most professionals did not have advanced knowledge regarding the national policy, undergraduate and postgraduate courses did not provide education on ethinic-racial relationships, health of the black population and related topics and the professional qualification is determining whether or not the professional will have an anti-racist performance. The knowledge of social determinants of health and the health of the black population imply in university professionals' practice of multidisciplinary teams in mental health which were investigated and should consider the unique and diverse characteristics of the served population, such as cultural, ethnic and racial aspects. It was observed the institutional racism is found in practice and discriminatory behavior in the work routine. Furthermore, it was also observed that the life experiences of professionals who declare themselves black and face racism imply in their practice; the permanent qualification can be the fundamental allied in preparation to an anti-racist practice in the health og black population; also, it is urgent the universities incorporate the DCNERER and PNSIPN in their undergraduate and postgraduate courses as well as local governments management and health institutions fulfill their responsibilities regarding the professional qualification.